Analysis of Nurses Knowledge and Motivation for the Implementation of Cardiopulmonary Resuscitation at Kaimana Hospital - Rahmania Ambarika; Nency Natalia Tho; Novita Ana Anggraini (Journal Of Nursing Practice, 2024)
Background: In carrying out cardiopulmonary resuscitation actions, compression accuracy and compression speed are required to be correct and appropriate in order to create a quality cardiopulmonary resuscitation series. Therefore, nurses’ knowledge and motivation are needed in carrying out cardiopulmonary resuscitation. Purpose: This research aims to determine the relationship between knowledge, motivation and accuracy in carrying out cardiopulmonary resuscitation. Method: This research uses a descriptive correlation research design with a cross sectional approach. With a purposive sampling technique, a sample of 49 respondents was obtained, the independent variables were knowledge and motivation, the dependent variable was cardiopulmonary resuscitation, using a questionnaire and observation sheet. The chi-square test was used to determine the relationship between the two variables. Results: The results of research from 49 respondents showed that the majority of respondents had moderate knowledge of 73.5%, moderate motivation of 59.2% and inappropriate RJP actions of 85.7%. Analysis using the chi-square statistical test on knowledge and motivation towards the implementation of cardiopulmonary resuscitation resulted in p = 0.000 ˂ 0.05, which means there is a relationship between knowledge and motivation towards the implementation of cardiopulmonary resuscitation measures. Conclusion: Knowledge has more influence on the implementation of RJP when compared to motivation, but in reality the level of knowledge is mostly in the medium category so it has an impact on the quality of RJP actions. The results will greatly influence health services to patients. Therefore, it must be supported by continuous learning or training in RJP techniques.